Targeted Private Well Outreach Following a Change in Drinking Water Standard: Arsenic and the New Jersey Private Well Testing Act. Issue 1 (27th January 2023) - O'Neill, Heidi S.; Flanagan, Sara V.; Gleason, Jessie A.; Spayd, Steven E.; Schwartz, Rebecca I.; Procopio, Nicholas A.
Abstract : Context: When the New Jersey Private Well Testing Act (PWTA) became effective in 2002, the maximum contaminant level (MCL) for arsenic in the United States was 50 μg/L. In 2006, the federal and New Jersey MCLs were lowered to 10 μg/L and 5 μg/L, respectively. Objective: To notify and provide free arsenic water testing for homeowners who had a PWTA arsenic result that passed for the MCL in 2006 or earlier but would exceed under the more health protective MCL enacted in 2006, which is still in effect as of this publication date. Design: About 1200 homeowners with PWTA arsenic results between 5 μg/L and 50 μg/L were offered free arsenic water testing. More than 400 homeowners requested tests and 292 returned samples. Setting: New Jersey, United States. Participants: Homeowners with a passing PWTA arsenic result before 2006 that would have failed under the New Jersey arsenic MCL enacted in 2006. Main Outcome Measures: Return rate of testing kits; number of tests exceeding arsenic MCL; and participant survey results. Results: Untreated well water samples (n = 279) were collected and 62.4% exceeded the New Jersey MCL. Treated well water samples (n = 102) were collected and 11.8% exceeded the current New Jersey MCL. In all, about 40% of drinking water samples from the tap, including those with or with no arsenic treatment, exceeded the New Jersey MCL. A survey of participants (n = 69) found that although many (67%) respondents reported that they at least had some idea that wells in their area are vulnerable to naturally occurring contaminants, such as arsenic, many (68%) reported that they had little or no idea that the New Jersey arsenic MCL had been lowered from 50 μg/L to 5 μg/L in 2006. Conclusions: This effort further illuminates the necessity and significance of public health outreach for private well water users, especially after drinking water standards change.